2019
DOI: 10.1590/18069657rbcs20180207
|View full text |Cite
|
Sign up to set email alerts
|

Relief Position and Soil Properties under Continuous Banana Cropping in Subhumid Climate in Northeast Brazil

Abstract: Sequences of thick and eroded soils in hills surfaces are cultivated with banana since the beginning of the last century in the Northeast of Pernambuco (PE), Brazil. Measurements of soil properties depending on soil slope under intensive agricultural cultivation are limited mostly as the pedogenetic approach. This study aimed to identify the dominant soil types, to evaluate morphological, physical, chemical, and mineralogical properties of soil profiles, and link them to the relief position under continuous ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The reduction in COT values is also evidenced when comparing the values prior to the implementation of the experiment, decreasing from 15 g kg -1 (Table 2) to 9.17 g kg -1 (Table 4), i.e., a 39% loss that was not reestablished even after 18 consecutive months of banana cultivation, possibly because, as a labile material, COT can be easily decomposed and removed during the rainy period and deposited at a lower elevation. Almeida et al (2019), observed similar results for COT in banana cultivation at different relief positions, with higher COT contents in the Fertility variability in a Latosol cultivated with fertigated banana middle third region (0-0.15 m depth), which was attributed to replacement and removal by water erosion. Soil organic matter is the most sensitive parameter for evaluating a management system and intimately relates to the CEC (SOLLY et al, 2020).…”
Section: Continuation Figuresupporting
confidence: 65%
See 2 more Smart Citations
“…The reduction in COT values is also evidenced when comparing the values prior to the implementation of the experiment, decreasing from 15 g kg -1 (Table 2) to 9.17 g kg -1 (Table 4), i.e., a 39% loss that was not reestablished even after 18 consecutive months of banana cultivation, possibly because, as a labile material, COT can be easily decomposed and removed during the rainy period and deposited at a lower elevation. Almeida et al (2019), observed similar results for COT in banana cultivation at different relief positions, with higher COT contents in the Fertility variability in a Latosol cultivated with fertigated banana middle third region (0-0.15 m depth), which was attributed to replacement and removal by water erosion. Soil organic matter is the most sensitive parameter for evaluating a management system and intimately relates to the CEC (SOLLY et al, 2020).…”
Section: Continuation Figuresupporting
confidence: 65%
“…The study was conducted in April 2017 at the Irrigation Perimeter Nupeba, managed by the Development Company of the São Francisco and Parnaíba Valleys (2020) in the municipality of Riachão das Neves (11°44'49''S and 11°54'23''W, 440 m of elevation), western Bahia. According to the current Köppen classifi cation, the climate is classifi ed as Aw, i.e., hot and semi-humid (ALVARES et al, 2013). The mean annual temperature is 27 °C, with a mean annual precipitation of 1,000 mm and a rainy season from October to April, with November, December, and January ranking as the rainiest months (INSTITUTO NACIONAL DE METEOROLOGIA, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation